Indexing resilience to heat and drought stress in the wild relatives of rapeseed-mustard - Kashyap, Anamika; Kumari, Sujata; Garg, Pooja; Kushwaha, Ranjeet; Tripathi, Shikha; Sharma, Jyoti; Gupta, Navin C.; Kumar, Rajeev Ranjan; Yadav, Rashmi; Vishwakarma, Harinder; Rana, Jai Chand; Bhattacharya, Ramcharan; et al. (MDPI, 2023)
Wild species are weedy relatives and progenitors of cultivated crops, usually maintained in their centres of origin. They are rich sources of diversity as they possess many agriculturally important traits. In this study, we analysed 25 wild species and 5 U triangle species of Brassica for their potential tolerance against heat and drought stress during germination and in order to examine the early seedling stage. We identified the germplasms based on the mean membership function value (MFV), which was calculated from the tolerance index of shoot length, root length, and biochemical analysis. The study revealed that B. napus (GSC-6) could withstand high temperatures and drought. Other genotypes that were tolerant to the impact of heat stress were B. tournefortii (RBT 2002), D. gomez-campoi, B. tournefortii (Rawa), L. sativum, and B. carinata (PC-6). C. sativa resisted drought but did not perform well when subjected to high temperatures. Tolerance to drought was observed in B. fruticulosa (Spain), B. tournefortii (RBT 2003), C. bursa-pastoris (late), D. muralis, C. abyssinica (EC694145), C. abyssinica (EC400058) and B. juncea (Pusa Jaikisan). This investigation contributes to germplasm characterization and the identification of the potential source of abiotic stress tolerance in the Brassica breeding programme. These identified genotypes can be potential sources for transferring the gene(s)/genomic regions that determine tolerance to the elite cultivars.